Encapsulation of catechin or curcumin in co-crystallized sucrose: Fabrication, characterization and application in beef meatballs. (1st October 2022) - Wang, Hengpeng; Gao, Sumin; Zhang, Di; Wang, Yinlan; Zhang, Yu; Jiang, Songsong; Li, Bing; Wu, Danxuan; Lv, Guanhua; Zou, Xiaobo; Meng, Xiangren
Abstract: Catechin and curcumin have high potential health benefits. In contrast, these free polyphenolic compounds are susceptible to the external environment, and curcumin's poor solubility further lowers its biological activity. Herein, catechin or curcumin was pre-emulsified with soybean protein isolate (SPI) and encapsulated in co-crystallized sucrose, respectively. The different encapsulated co-crystals were applied to beef meatballs as antioxidants and emulsifiers. DSC, XRD, FTIR, and SEM confirmed the modification from crystalline to irregular agglomerates after co-crystallization treatment. Co-crystallization with encapsulated catechin (CCA, CSCA) showed higher total phenolic content (over 210 mg GAE/100 g) and free radicals scavenging activity (over 87%) than that in encapsulated curcumin. The beef meatballs added with encapsulated catechin (MCCA) had the lowest TBARS (0.158 mg MDA·kg −1 ) and carbonyl content (0.282 nmol/mg) but the highest total sulfhydryl content (995.88 nmol/mg), and total in vitro digestibility (96.47%). Notably, encapsulated SPI-catechin or SPI-curcumin (CSCA, CSCU) significantly improved the emulsification effect of beef meatballs by maintaining the lower cooking loss, higher water-holding capacity, and better texture properties, as evident from LF-NMR, light microscopy images and protein solubility. In conclusion, co-crystallization significantly improved the stability of catechin and curcumin, and applying these co-crystals in meat products as natural antioxidants and emulsifiers is feasible. Highlights: Co-crystallization process does not change the chemical structure of active compound. The presence of SPI enhances the co-crystals antioxidation and emulsification. Co-crystallized catechin is better for improving the quality of beef meatball.